STUDI KOMPARATIF ANTARA TEORI BELAJAR DALAM PERSPEKTIF BARAT DAN ISLAM - Arsyadana, Addin (STAIN Kediri, 2015)
Learning is a necessity and plays an important role because human beings are born weak who do not know and cannot do anything; they only have physical and spiritual potential (QS. al-Naḥl [16]: 78). Therefore, human beings are affected by how they are learning in which reason is the most vital element in their learning processes. A number of learning theories have been produced due to the urgency of learning which are categorized into two paradigms: the West and the East (Islam). This article attempts to examine comparatively the two perspectives of learning theories and their influence on Islamic education in particular. This article argues that even though Western learning theories have different orientations from that of Islam, Muslims still adopt those theories uncritically, even in Islam based universities which are still applying conventional learning theories.Keywords: Teori Belajar, Barat, Islam